The beneficial effect of acromegaly control on blood pressure values in normotensive patients. (5th May 2014) - Sardella, Chiara; Urbani, Claudio; Lombardi, Martina; Nuzzo, Alessandro; Manetti, Luca; Lupi, Isabella; Rossi, Giuseppe; Del Sarto, Simone; Scattina, Ilaria; Di Bello, Vitantonio; Martino, Enio; Bogazzi, Fausto
Summary Objective Control of acromegaly may ameliorate blood pressure (BP) in hypertensive (HT) patients. We evaluated the impact of acromegaly control on BP values of normotensive (NT) acromegalics. Design Retrospective cohort study. Patients Fifty‐eight naïve patients with acromegaly (39 F; age range, 30–69 years), including 28 NT and 30 HT subjects, participated in the study. Measurements Blood pressure was measured by clinical measurement and 24‐h ambulatory monitoring at diagnosis and after 24 months of medical therapy for acromegaly. Results Acromegaly was controlled by medical therapy in 15 NT and 17 HT patients at 24 months. In the NT group, systolic (SBP) or diastolic (DBP) BP significantly increased (all P < 0·005) when acromegaly was uncontrolled, but did not change when the disease was controlled. Changes in SBP and DBP were also significantly different between uncontrolled and controlled NT patients. At 24 months, clinical hypertension was detected only in uncontrolled NT patients (46% vs 0%, P < 0·001), whereas ambulatory hypertension was found in 38% of uncontrolled and in 7% of controlled NT subjects (P = 0·035). In the HT group, ambulatory SBP increased in patients with uncontrolled acromegaly (24‐h SBP P = 0·046, day SBP P = 0·005, night SBP P = 0·005), whereas ambulatory DBP decreased in subjects with controlled disease (24‐h DBP P = 0·008, day DBP P = 0·026). Conclusions Control of acromegaly has a beneficial effect on BP regulation either in HT or NT subjects; in the latter, it may prevent progression towards hypertension.